2007
DOI: 10.1103/physreve.75.026212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of random bulk inhomogeneities on quasioptical cavity resonator spectrum

Abstract: The statistical spectral theory of oscillations in a quasioptical cavity resonator filled with random inhomogeneities is suggested. It is shown that inhomogeneities in the resonator lead to intermode scattering which results in the shift and broadening of spectral lines. The shift and the broadening of each spectral line is strongly depended upon the frequency distance between the nearest-neighbor spectral lines. As this distance increases, the influence of inhomogeneities is sharply reduced. Solitary spectral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…[2]. In this technique, for each of the modes the "seed" (or trial) mode propagator ( ) V G  is introduced, which represents the mode Green function calculated with no regard for inter-mode scattering, viz.,…”
Section: Separation Of Oscillatory Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]. In this technique, for each of the modes the "seed" (or trial) mode propagator ( ) V G  is introduced, which represents the mode Green function calculated with no regard for inter-mode scattering, viz.,…”
Section: Separation Of Oscillatory Modesmentioning
confidence: 99%
“…Then, using the operator technique developed in Ref. [2], strict separation of oscillatory modes is performed at arbitrary level of inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The technique was first elaborated in Ref. [24] for the open systems of waveguide configuration and then expanded to open-ended and closed resonator-type systems disordered in the bulk [25] as well as on the surface [13,26]. With regard to the waveguidetype systems, the method reduces (schematically) to the following action sequence.…”
Section: Mode Separation In the Waveguide With Nonuniform Segmentmentioning
confidence: 99%
“…The region includes the extended states of only first stability band of solutions to equation (20), as well as the evanescent states with negative mode energies. In terms of physical parameters of the system at hand, the inequalities (25) suggest the relative smallness of the corrugation amplitude and the smallness of its period against the wave length, i. e., the fulfillment of inequalities…”
Section: Figmentioning
confidence: 99%
“…In our recent papers, Refs. [9][10][11], using the method developed previously in Ref. [12] we have shown that one can separate variables in a wave equation and thus perform a comprehensive spectral analysis, for any restricted wave system, however disordered, lossy, or lossless it may be.…”
Section: Introductionmentioning
confidence: 99%